Favoring 7th Graders’ Performance in Oral Assessment Tasks in the English Class - Gallego Barrera, Edier Alejandro; Castrillón Quintero, Jairo Alonso; Giraldo Montoya, Marisol; Gómez Henao, Lina Marcela (Universidad Cátolica Luis Amigó, 2020)
This was a qualitative exploratory study aimed at describing how a 7th-grade class faced oral assessments in the English class. Data collection instruments included a diagnostic oral assessment task, three questionnaires, class observations and a research journal. They allowed to generate information about participants’ emotions and practices before and during oral assessments in the English, as well as their perceptions of the phenomena. Results revealed that students’ negative emotions can interfere in their performance when facing oral assessment tasks. Therefore, the teacher implemented different strategies in order to cope with these negative emotions to favor students’ performance.
Keywords: Oral assessment; oral tasks; Strategies; Oral performance; Emotions; a